2019
DOI: 10.1111/cpf.12595
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial structure and function predictors of recurrent fibrillation after catheter ablation: a systematic review and meta‐analysis

Abstract: Background Catheter ablation (CA) has become a conventional treatment for atrial fibrillation (AF), but remains with high recurrence rate. The aim of this metaanalysis was to determine left atrial (LA) structure and function indices that predict recurrence of AF. Methods We systematically searched PubMed-Medline, EMBASE, Scopus, Google Scholar and the Cochrane Central Registry, up to September 2017 in order to select clinical trials and observational studies which reported echocardiographic predictors of AF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 118 publications
2
18
0
3
Order By: Relevance
“…The cause for better relationship between LASRa and PCWP in post-capillary PH is probably due to the nonlinear relationship between LASRa and PCWP in the whole group. In adhering with previous studies and meta-analyses that reported LASs as the strongest predictor of cavity pressure and recurrent arrhythmia [26,27], the compromised LA strain rate during atrial contraction, we found, could be seen as directly reflecting LA myocardial dysfunction. This finding should indeed be considered in a fashion parallel to the left ventricle.…”
Section: Data Interpretationsupporting
confidence: 86%
“…The cause for better relationship between LASRa and PCWP in post-capillary PH is probably due to the nonlinear relationship between LASRa and PCWP in the whole group. In adhering with previous studies and meta-analyses that reported LASs as the strongest predictor of cavity pressure and recurrent arrhythmia [26,27], the compromised LA strain rate during atrial contraction, we found, could be seen as directly reflecting LA myocardial dysfunction. This finding should indeed be considered in a fashion parallel to the left ventricle.…”
Section: Data Interpretationsupporting
confidence: 86%
“…The emptying of the diastolic LAA in AF was linked to and projected a good LA booster pump function (37). The LAA structure changes that precede LA remodeling, both in terms of operation and morphology, have been shown to predict AF recurrence (12,14). Based on the hemodynamic activity of the LAA and the findings of our work, we think that the LAA is a much more sensitive criterion for the prediction of AF recurrence than morphological remodeling or LA functional in the LA.…”
Section: Discussionmentioning
confidence: 53%
“…Certain variables, such as AF duration (8), body mass index (BMI) (9), high blood pressure (10), diabetes mellitus (11), left atrial (LA) diameter (12,13), LA strain (14), and other echocardiographic indexes (15,16) can play a role in predicting ablation outcomes. However, no valid parameter exists to forecast AF recurrence following ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Limited increases in cavity size in diastole are associated with raised diastolic pressures which chronically result in the perpetual rise of LA pressures, increase in cavity volume and myocardial stretch [27,28]. These structural changes are bound to eventually compromise LA's intrinsic myocardial properties, reduce cavity deformation and increase its stiffness and fibrosis [28][29][30]. The end result of such abnormalities is the dilatation of mitral annulus, worsening mitral regurgitation, pulmonary venous hypertension and, later on, pulmonary arterial hypertension [31].…”
Section: Resultsmentioning
confidence: 99%